2003
DOI: 10.1046/j.1601-1848.2003.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of genetic variation in serotonergic neurotransmission

Abstract: Serotonin (5-hydroxytryptamine; 5-HT) is a potent modulator of the physiology and behavior involved in generating appropriate responses to environmental cues such as danger or threat. Furthermore, genetic variation in 5-HT subsystem genes can impact upon several dimensions of emotional behavior including neuroticism and psychopathology, but especially anxiety traits. Recently, functional neuroimaging has provided a dramatic illustration of how a promoter polymorphism in the human 5-HT transporter (5-HTT) gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 82 publications
1
63
0
3
Order By: Relevance
“…A sample size of 35 subjects is a small number for a genetic study, but it is a large sample for a PET study and is consistent numerically with other recent neuroimaging studies showing plausible associations between polymorphisms and other imaging parameters such as functional magnetic resonance imaging responses to emotional face recognition (Hariri et al, 2002). Indeed, it has been suggested that emotional and affective neural systems, which can be imaged, may be more directly related to 5-HT functional polymorphisms than complex behaviors or psychiatric syndromes (Hariri and Weinberger, 2003). Although the validity of post hoc power calculations are debatable (Goodman and Berlin, 1994;Hoenig and Heisey, 2001), our power calculations showed that, for the 5-HT 1A receptor gene (Ϫ1018) CϾG SNP, we had a power of 89% to detect a 15% difference of BP between groups, with ␣ ϭ 0.05.…”
Section: Discussionsupporting
confidence: 84%
“…A sample size of 35 subjects is a small number for a genetic study, but it is a large sample for a PET study and is consistent numerically with other recent neuroimaging studies showing plausible associations between polymorphisms and other imaging parameters such as functional magnetic resonance imaging responses to emotional face recognition (Hariri et al, 2002). Indeed, it has been suggested that emotional and affective neural systems, which can be imaged, may be more directly related to 5-HT functional polymorphisms than complex behaviors or psychiatric syndromes (Hariri and Weinberger, 2003). Although the validity of post hoc power calculations are debatable (Goodman and Berlin, 1994;Hoenig and Heisey, 2001), our power calculations showed that, for the 5-HT 1A receptor gene (Ϫ1018) CϾG SNP, we had a power of 89% to detect a 15% difference of BP between groups, with ␣ ϭ 0.05.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, finding evidence for transmission of polymorphic alleles of the 5-HTT may depend on the extent of social and communication deficits in the autism proband, suggesting that the alleles may modify severity of autistic traits rather than conveying risk for autism per se [Tordjman et al, 2001]. Further support for 5-HTT comes from functional MRI studies showing that individuals with one or two copies of a short allele of the gene had greater neuronal activity than controls in the amygdala, a brain region implicated in autism [Hariri et al, 2002;Hariri and Weinberger, 2003]. In addition, multiple single polymorphisms in tryptophan 2,3 diooxygenase (TDO2), the rate-limiting enzyme in L-tryptophan catabolism, have been associated with autism.…”
Section: Serotoninmentioning
confidence: 99%
“…Indeed, several investigations including an 'oddball' task-generated P300 waveform study of healthy controls and patients with schizophrenia [24] suggest the presence of increased dopaminergic cortical signalling, enhanced signal/noise ratio, and optimized cortical activity, conferred by the Met allele, during processing tasks of different nature [18,25,39,47]. Two brain imaging studies of healthy adults showed an influence of the COMT Val158Met genotype on task-related brain activation.…”
Section: Introductionmentioning
confidence: 99%